Effects of different arm immobilization methods on set-up accuracy in photon and proton radiotherapy techniques for breast cancer: A systematic review - Hadisinia Tahereh; Abbaspour Samira; Abedi-Firouzjah Razzagh (Archive of Oncology)
This study aimed to review the effects of different arm immobilization methods on set-up accuracy in photon and proton radiotherapy techniques for breast cancer with supraclavicular lymph node (LN) involvement. A systematic review was conducted using a comprehensive literature search of English-language sources from PubMed, Google Scholar, ScienceDirect, and Medline databases, with no restrictions on publication date. Two independent reviewers assessed and screened titles and abstracts for inclusion. Following screening and eligibility determination, 14 articles were included. Of these, 11 studies focused on photon radiotherapy (8 in the supine position and 3 in the prone position), while 3 studies examined proton radiotherapy. For the supine position, the "both hands above the head" method demonstrated superior set-up accuracy. In the prone position, the crawl position combined with the deep inspiration breath-hold (DIBH) method outperformed other approaches. In proton radiotherapy for breast cancer, both "hands-up" and "hands-down" methods yielded equivalent results.